Accidental and Programmed Cell Death in Investigative and Toxicologic Pathology. Issue 1 (30th April 2018) - Radi, Zaher A.; Stewart, Zachary S.; O'Neil, Shawn P.
Abstract: Cellular development and homeostasis are regulated via programmed cell death (PCD; apoptosis), which is a genetically regulated cellular process. Accidental cell death (ACD; necrosis) can be triggered by chemical, physical, or mechanical stress. Necrosis is the presence of dead tissues or cells in a living organism regardless of the initiating process and can be observed in infectious and non‐infectious diseases and toxicities. This article describes tissue‐based immunohistotechnical protocols used for assessing PCD and necrosis in formalin‐fixed tissues obtained from preclinical species used in investigative and toxicologic pathology. Two commonly employed protocols for the identification of PCD and necrosis are described in this article: immunohistochemistry (IHC) for cleaved caspase 3, and terminal deoxynucleotidyl transferase (TdT)‐mediated dUTP nick‐end labeling (TUNEL). TUNEL has been used to detect DNA fragmentation by labeling the terminal ends of nucleic acids in necrotic and apoptotic cells. © 2018 by John Wiley & Sons, Inc.